Infertility - Nasriddinova Shakhzoda; El'muradova Durdona; Nasriddinova Xonzoda; Abdixalilov Mirziyo; Bekturdiev Rustambek; Kamolov Rustamjon; Salimova Dildora Erkinovna (Zien Journals, 2023)
Infertility is generally defined as the inability of a couple to conceive a child even after one year of frequent unprotected sex.[1] It affects about 15% of all couples in the United States and at least 180 million worldwide. Male infertility is defined as a man's inability to make a fertile woman pregnant after at least one year of unprotected intercourse. Men are solely responsible for approximately 20% and are a contributing factor in another 30% to 40% of all cases of infertility.[3] Because male and female causes often coexist, it is important that both partners are evaluated for infertility and treated together. In general, the male factor makes a significant contribution to approximately 50% of all cases of infertility
Keywords: Sexual dysfunction; hypogonadism; oligozoospermia; asthenozoospermia